Characterization of Water Solubility and Binding of Spin Labeled Drugs in the Presence of Albumin Nanoparticles and Proteins by Electron Paramagnetic Resonance Spectroscopy. Issue 6 (10th February 2022) - Sozer, Sumeyra C.; Akdogan, Yasar
Abstract: Electron paramagnetic resonance (EPR) spectroscopy is an advantageous technique to monitor solubility of drugs in an aqueous solution. In the presence of a drug carrier, the bound and unbound drug fractions can be determined in the same sample simultaneously. To enhance the solubility of hydrophobic drugs, a transporter protein of bovine serum albumin (BSA) can be used directly or in the form of nanoparticle. Moreover, a cationic BSA can be used to enhance anionic drug loading. Here, drugs with different water solubility, salicylic acid (high), ibuprofen (low) and chlorambucil (none) were spin labeled and studied with EPR spectroscopy. Remarkably, it has been shown that albumin nanoparticles are much more effective than albumin proteins in dissolving hydrophobic drugs in water. Furthermore, different drug loading methods were compared, and different from other techniques drug release can be monitored directly from the NPs pellet dissolution by EPR spectroscopy. Abstract : EPR spectroscopy as an alternative technique monitors drugs in solution. Water‐soluble albumin nanoparticles disturb undissolved drug aggregates, which enhances hydrophobic drug solubility. EPR combined with spin labeling of drugs provides distinguishing three forms of drugs such as undissolved, dissolved unbound and bound forms, which can be determined simultaneously. Detecting all forms of drugs in one measurement provides a more accurate result.